Intracranial pressure telemetry: first experience of an experimental in vivo study using a new device - Orakcioglu, Berk; Beynon, Christopher; Kentar, Modar; Sakowitz, Oliver (Intracranial pressure and brain monitoring XIV, 2012)
To test two new telemetric intracranial pressure (ICP) probes (NEUROVENT®-P-tel, NEUROVENT®-S-tel) in a porcine model. We aimed to intraoperatively correlate the telemetric probes to parenchymal ICP probes and study their reliability in the first hours after implantation. The experimental set-up, new telemetric technology and first data will be presented.